The influence of yoga excercise towards blood pressure in patient hypertension - witriyani, witriyani (Sahabat Publikasi Kuu, 2023)
Background: The incidence of hypertension in Indonesia, aged 18 years and over, is 34.1%. Hypertension majority is experienced more by people who live in urban areas than in rural areas as seen from the prevalence of hypertension of 34.4% of the population living in urban areas while the population living in rural areas is 33.7%. One effort to treat non-pharmacological hypertension that can be done is giving yoga. Objective: To determine the influence of yoga exercises on reducing blood pressure in hypertensive patients at Puskesmas Musuk 1 Boyolali. Method: The research type of this study is a quasi-experimental using a one-group pretest-posttest design. The sampling technique used was purposive sampling of 24 respondents. The research instruments used were SOP yoga and pretest-posttest blood pressure observation sheets. The data analysis was tested by using the Wilcoxon Test. Results: Most of the blood pressure in hypertensive patients before being given yoga was in the moderate category as many as 24 respondents (100%) and after being given yoga exercise, most of the hypertensive patients were in the normal category as many as 13 respondents (54.2%). Conclusion: There is an effect of yoga on reducing blood pressure in hypertensive patients at Puskesmas Musuk 1 marked by p-value = 0.000 (p <0.05)